A study to determine the palliative care needs of patients with drug resistant tuberculosis in the Southern sub-district of Cape Town - Odell, Shannon (Division of Family Medicine, 2019)
Introduction: The Palliative Care needs of patients with Drug-Resistant Tuberculosis (DR-TB) are under-researched, yet pertinent in the management and control of DR-TB. Most literature reviewed focused on treatment schedules, outcomes, transmission, drug adherence, drug side effects and further drug-resistance. Aim: The aim was to determine the palliative care needs of patients infected with DR-TB living in the Southern sub-district of Cape Town. The Objectives The objectives were to determine the quality of life and symptom burden of DR-TB patients and to assess for correlation between these variables and palliative care needs. Methodology: In this cross-sectional study, twenty-eight participants were posed a culturally sensitive questionnaire designed by the researcher, that comprised: demographic questions, Likert-type questions for the African Palliative Care Association – Palliative Outcome Score (APCA-POS) tool, Eastern Co-operative Oncology Group (ECOG) score, a symptom checklist and open patient dignity questions. Quantitative and qualitative data of the respondents’ quality of life, functional status and burden of symptoms in the preceding week were ascertained. Pre-determined numerical scores in the Likert-type questions were deemed indicative of palliative care need. Results: Quantitative and qualitative analysis of the data showed that each participant had a palliative care need: be it either (or a combination of) unmet clinical, psychological, social and/or spiritual needs - despite being at differing stages of the DR-TB disease trajectory. These needs required contextualizing within the respondents’ communities where socio-economic issues were prevalent. Predominant physical complaints were tiredness (79%), joint pain (64%), confusion (61%) and shortness of breath (51%). Respondents’ also experienced a loss of autonomy, poor self-value and financial insecurity. Fifty percent of patients interviewed required urgent further management and referral to the local clinic. Conclusion: Despite the small cohort of patients and possible recruitment bias, this research concurred that a palliative care approach be adopted from the point of DR-TB diagnosis and throughout the treatment period – regardless of treatment outcome; and that DR-TB patients had significant unmet palliative care needs that affected their quality of life, functional status and dignity, regardless of whether pain was present.